2017
DOI: 10.3201/eid2305.161720
|View full text |Cite
|
Sign up to set email alerts
|

Translation of Real-Time Infectious Disease Modeling into Routine Public Health Practice

Abstract: Infectious disease dynamic modeling can support outbreak emergency responses. We conducted a workshop to canvas the needs of stakeholders in Australia for practical, real-time modeling tools for infectious disease emergencies. The workshop was attended by 29 participants who represented government, defense, general practice, and academia stakeholders. We found that modeling is underused in Australia and its potential is poorly understood by practitioners involved in epidemic responses. The development of bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 31 publications
0
39
0
5
Order By: Relevance
“…We understand that there are trade-offs between the use of sophisticated modelling techniques and simple method in generating outputs for forecasting of influenza epidemics/outbreaks. Although studies have shown the potential benefits of using advanced modelling statistics in this area, and yet most public health practitioners do not use such methods and rely on descriptive data [21]. There are many reasons, and some may due to the lack of proper training or knowledge in modelling and uncertainty of modelling; these may hinder the efficient use of such tools [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We understand that there are trade-offs between the use of sophisticated modelling techniques and simple method in generating outputs for forecasting of influenza epidemics/outbreaks. Although studies have shown the potential benefits of using advanced modelling statistics in this area, and yet most public health practitioners do not use such methods and rely on descriptive data [21]. There are many reasons, and some may due to the lack of proper training or knowledge in modelling and uncertainty of modelling; these may hinder the efficient use of such tools [21].…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have shown the potential benefits of using advanced modelling statistics in this area, and yet most public health practitioners do not use such methods and rely on descriptive data [21]. There are many reasons, and some may due to the lack of proper training or knowledge in modelling and uncertainty of modelling; these may hinder the efficient use of such tools [21]. There is also a need in the area to engage health system stakeholders involved in operational response and to improve uptake of such tools for decision support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing interest and popularity around more collaborative and co-productive way of formulating evidence translation (ET) research should be balanced with some of the challenges [1]. This includes asking the question whether all research endeavours lend themselves to this approach.…”
Section: Introductionmentioning
confidence: 99%
“…However, perhaps the answer to this question for some would rest on what gets counted as science, although any applied research may also receive the same criticisms about generalizability, universality and objectivity. However, there may be research agendas, or incremental and discrete research studies within these agendas, that require collaborative and participative partnership [1,2].…”
Section: Introductionmentioning
confidence: 99%